Diels‐alder click reaction for the preparation of polycarbonate block copolymers. Issue 10 (19th February 2013) - Omurtag, Pinar Sinem; Gunay, Ufuk Saim; Dag, Aydan; Durmaz, Hakan; Hizal, Gurkan; Tunca, Umit
Abstract The Diels‐Alder reaction as a click reaction strategy is applied to the preparation of well‐defined polycarbonate (PC)‐block copolymers. A well‐defined α‐anthracene‐terminated polycarbonate (PC‐anthracene) is prepared using 9‐anthracene methanol as an initiator in the ring opening polymerization of benzyl 5‐methyl‐2‐oxo‐1, 3‐dioxane‐5‐carboxylate in CH2Cl2 at room temperature for 5 h. Next, a well‐defined α‐furan protected maleimide‐terminated‐poly(ethylene glycol) (PEG11‐MI or PEG37‐MI), ‐poly(methyl methacrylate) (PMMA26‐MI), and ‐poly(ε‐caprolactone) (PCL27‐MI) were clicked with the PC‐anthracene at reflux temperature of toluene to yield their corresponding PC‐based block copolymers (PC‐b‐PEG, PC‐b‐PMMA, and PC‐b‐PCL). The homopolymer precursors and their block copolymers were characterized by using the GPC, NMR and UV analysis. © 2013 Wiley Periodicals, Inc. J Polym Sci Part A: Polym Chem, 2013